TAREKAT SAMMANIYAH DI PALEMBANG - Zulkarnain Yani (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract:This paper describes the study of the history and development of the Sammaniyah tarekat, that appear in Palembang, accompanied by the leader of Sammaniyah in Palembang. This study is interesting in view of the lack of accurate and valid references on the development of the Sammaniyah in Palembang. It is brought by one of the famous scholars Palembang, namely Shaykh 'Abd al-Samad al-Jawi al-Falimbani. The tarekat is becoming very famous in Palembang people with various religious rituals, which  are performed at the Great Mosque in Palembang and religious social life of everyday people of Palembang.  Keywords: -path for mystics to follow, -Sammaniyah, -Palembang.